Pemetaan Kerusakan Jalan Menggunakan Metode Pavement Condition Index dan Metode Bina Marga - Subhan Mulyana; Athaya Zhafirah; Isne Nabila Permata Sari (Jurnal Konstruksi, 2025)
Kamojang Garut Highway is a district road that serves as an alternative route between Bandung and Garut, passing through tourist and industrial areas. This road has suffered various types of damage, such as cracks, potholes, and deformation, which have reduced service quality and disrupted the socio-economic activities of the community. This study evaluates the condition of the road from STA 0+000 to STA 8+300 using the Pavement Condition Index (PCI) and Bina Marga methods. The PCI method involves a field survey to identify the type, severity, and extent of damage, then calculates the pavement condition index. The Bina Marga method assesses damage based on the road condition classification from the Directorate General of Highways. The results show an average PCI value of 43.37%, with a “fair” road surface condition that requires overlay. Based on Bina Marga, a damage score of 11 results in a condition value of 4, indicating priority for periodic maintenance. Mapping based on the Geographic Information System (GIS) using QGIS illustrates the spatial distribution of damage in detail, facilitating the identification of priority locations. This combination of methods provides a comprehensive, detailed, and applicable evaluation. The results of this study are expected to serve as a reference for local governments for more effective, efficient, and sustainable road repairs.